Governing Spatial Disparities in School Infrastructure by Numbers: Investments in Form, Tensions, New Compromises? - Walter Bartl (MDPI AG, 2022)
Given that education infrastructure has been a crucial element of the infrastructural power of the welfare state, surprisingly little is known about how spatial disparities in school infrastructure have been governed. While emphasis has recently been placed on the role of numbers in governing the education system, there have been contradictory results on the use of numbers for measuring spatial disparities in schooling on the one hand and on allocating school infrastructure by numbers on the other. What role have indicators played in the governance of regional disparities in education and how can we explain changes to this role? Assuming that indicators typically fulfil two functions in decision making processes (information gathering and allocation of resources), this article develops an ideal-typical distinction between four ways of (not) using numbers for governance purposes. This typology is applied to a historical case study of indicators as a device for governing spatial disparities in education in Germany. Cognitive investments in indicators for observing spatial disparities in education and for administering schools have been made in Germany since the early 19th century. However, conceptual flaws and conservative education policies have kept them from being put to effective practice in school infrastructure policies. It was not until the 1970s that demographic and administrative indicators became institutionalized as part of decentralized but fairly standardized school planning practices. While the use of indicators in the spatial allocation of education resources seemed to work well during periods of educational expansion, this calculative practice produced tension with the civic idea of spatial justice when enrolments declined.